The editing of Louis Adamic's book The Eagle and the Roots - Janja Žitnik Serafin (Acta Neophilologica, 1989)
The Eagle and the Roots is Louis Adamic's last book and, in his own opinion, his most important one. The printed version of that work is an expurgated version of the author's typescript which is preserved in several incomplete copies, kept in various public and private archives in Yugoslavia and in the United States. The work was written on the basis of the author's personal impressions during his second visit to his native land in 1949. The published version of The Eagle and the Roots discusses the political and economic conditions in Yugoslavia in 1949, the moods of the Yugoslav people, their top politicians and intellectuals at the time of the first five-year plan (Book One), including a biography of Josip Broz Tito until 1945 with an outline of the most important events in the country before and during World War II (Book Two). In various passages scattered in both books, it describes the selfsacrifice and the resistance of the Yugoslav people during the Liberation War. An important subject is the dissention between Tito and Stalin which had its germs in the prewar period. The author follows its development through the war and during the first years after the liberation until the Cominform resolution in June 1948.